2019
DOI: 10.20937/rica.2019.35.esp01.14
|View full text |Cite
|
Sign up to set email alerts
|

On Odour Emission Rate From the Working Area of a Municipal Solid Waste Landfill in China

Abstract: To investigate the odour emission rate from the surface of a municipal solid waste landfill working area in China, a wind tunnel sampler was used to measure the emission rates of volatile organic compounds (VOCs), H2S and odour units. The results showed that the odour emission rate from the non-point source landfill is closely connected with the environmental temperature and the velocity of surface sweeping. In summer, the emission rates of VOCs (measured by PID as isobutylene), H2S and odour units are 385-680… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…e rise of temperature would reduce the atmospheric stability which may weaken the pollutant vertical convection in the air. Qiang et al reported that the concentration of odorous gas in spring and summer was significantly higher than that in autumn and winter [32].…”
Section: Air Temperaturementioning
confidence: 99%
“…e rise of temperature would reduce the atmospheric stability which may weaken the pollutant vertical convection in the air. Qiang et al reported that the concentration of odorous gas in spring and summer was significantly higher than that in autumn and winter [32].…”
Section: Air Temperaturementioning
confidence: 99%
“…In this study, H 2 S was used as the tracer gas. The emission rate of H 2 S in a landfill in summer was 4-7 µg/(m 2 •s) [44], which was affected by waste volume, temperature, ventilation and other factors. Taking the correction coefficient of 50%, the emission rate of H 2 S in the residential area was 2-3.5 µg/(m 2 •s).…”
Section: Test Case Descriptionmentioning
confidence: 99%